THE LEGAL BASIS OF THE GUARANTEE OF THE RIGHT TO SHARE HUMAN BEING - Abdusattarova Farangiz; Najmutdinova Mehrangiz (American Journals Publishing, 2024)
The article describes the role and importance of the Universal Declaration of Human Rights and the Constitution of the Republic of Uzbekistan as the legal basis of guarantees of the right to citizenship. It was also emphasized that human rights are an important constitutional institution and their provision and guarantees in a democratic-legal state.
Keywords: Man, human rights, Constitution, Universal Declaration of Human Rights, rights and freedoms, guarantee, citizen, citizen of Uzbekistan, legal state, citizenship.